2014
DOI: 10.3855/jidc.3746
|View full text |Cite
|
Sign up to set email alerts
|

Detection of plasmid-mediated qnr genes among the quinolone-resistant Escherichia coli isolates in Iran

Abstract: Introduction: Plasmid-mediated quinolone resistance, which complicates treatment, has been increasingly identified in Escherichia coli isolates worldwide. The purpose of this study was to identify the plasmid-mediated qnrA and qnrB genes among the quinolone-resistant Escherichia coli isolated from urinary tract infections in Iran. Methodology: A total of 140 Escherichia coli isolates were collected between March and October 2012 from urinary tract infections in Khorram Abad, Iran. All isolates were tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
3
20
2
Order By: Relevance
“…In a study conducted on quinolone resistance amongst E. coli strains isolated from UTI by Firoozeh et al, (2013) frequencies of qnrA and qnrB in nalidixic acid-resistant isolates were 12.1% and 7.8% and also in ciprofloxacin-resistant isolates, these were 22.2% and 14.3%, respectively (33). However, in the present study, the prevalence of qnrA and qnrB was 3.3% and 1.4% respectively.…”
Section: Discussioncontrasting
confidence: 50%
“…In a study conducted on quinolone resistance amongst E. coli strains isolated from UTI by Firoozeh et al, (2013) frequencies of qnrA and qnrB in nalidixic acid-resistant isolates were 12.1% and 7.8% and also in ciprofloxacin-resistant isolates, these were 22.2% and 14.3%, respectively (33). However, in the present study, the prevalence of qnrA and qnrB was 3.3% and 1.4% respectively.…”
Section: Discussioncontrasting
confidence: 50%
“…Quinolones are the most widely used antibacterial agents in fighting against serious infections caused by E. coli and other members of Enterobacteriaceae in Iran [19]. However, plasmid-mediated quinolone resistance in the genus belonging to Enterobacteriaceae, especially E. coil , has led to treatment failures and currently is becoming a significant public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were partly similar to the resistance levels reported in two previously conducted studies in Iran. Firoozeh et al [19] reported that 82.5% and 45% of urinary E. coli isolates were resistant to nalidixic acid and ciprofloxacin, respectively. In another study from Iran, Khorvash et al [21] found that 76% and 52% E. coli isolates associated with nosocomial infection were resistant to nalidixic acid and ciprofloxacin, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over one million cases of CAUTIs are reported annually, and CAUTIs account for about 80% of all nosocomial UTIs cases [3]. Escherichia coli is the most common cause of UTIs, accounting for 80%-90% of all UTIs seen among outpatients [4]. Uropathogenic Escherichia coli (UPEC) strains are known as the most frequent causative agent of UTIs [5].…”
Section: Introductionmentioning
confidence: 99%